Mastering VBA for Microsoft Office 2010 - Mansfield, Richard 1945- (Wiley Pub., 2010)
"A comprehensive guide to the language used to customize Microsoft Office Visual Basic for Applications (VBA) is the language used for writing macros, automating Office applications, and creating custom applications in Word, Excel, PowerPoint, Outlook, and Access. This complete guide shows both IT professionals and novice developers how to master VBA in order to customize the entire Office suite for specific business needs. Office 2010 is the leading productivity suite, and the VBA language enables customizations of all the Office programs; this complete guide gives both novice and experienced programmers the knowledge they need to make maximum use of VBA for Office Supported with real-world examples in Word, Excel, PowerPoint, Outlook, and Access, this book offers clear, systematic tutorials with both intermediate and advanced content Covers learning how to work with VBA; recording macros; using loops and functions; using message boxes, input boxes, and dialog boxes; creating effective code; XML-based files; ActiveX; the developer tab; content controls; add-ins; embedded macros; and security Mastering VBA for Office 2010 prepares developers to customize all Microsoft Office 2010 applications for the unique needs of their employers."--Provided by publisher.